Dialog prawosławno-protestancki na ziemiach ruskich I Rzeczypospolitej (przełom XVI i XVII w.) - Melnyk, Marek (Przegląd Wschodnioeuropejski, 2023)
The article presents the main directions of the “strategy” of the Orthodox and Protestant dialogue and cooperation in the Ruthenian territories of the Polish-Lithuanian Commonwealth (at the turn of the 16th and 17th centuries). This cooperation was undertaken too late. It took place at the time of the predominance of the counter-reformation camp in the Polish-Lithuanian Commonwealth. It had therefore an ad hoc character. At the same time, it was severely criticized. Describing the image of the Orthodox and Protestant cooperation inspired by political problems should be separated from strictly theological issues.